Some physical and chemical properties of the murat river’s section between Palu district and gülüşkür region - Çağlar, M. (Green Wave Publishing of Canada, 2019)
In this study, the water quality and diatoms of the Murat River’s section between Palu district and Gülüşkür region were analyzed between March 2010 - February 2011. 4 stations were identified for the study. Water samples were collected from the stations to determine the chemical properties of the river. The analyses and measurements carried out for this thesis study have revealed that according to water quality criteria the Murat River has clean water characteristics. On the other hand, the total amount of phosphorus and the number of coliform bacteria have pointed to the danger of eutrophication in the Murat River according to the Water Pollution Control Regulation. © 2019, Green Wave Publishing of Canada. All rights reserved.
Keywords: Chemical parameters; Elazığ; Murat River; Water Quality